The Moral Foundations of Islamic Economics: An Analysis of Al-Maududi’s Thought - Ade Jamarudin; Muh. Said; Syafi'ah Syafi'ah; Didin Komarudin; Imam Sucipto (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study analyzes the contribution of Abu al-A'la al-Maududi's thought related to Islamic morality in the Islamic economic system. The background of this study departs from the failure of the conventional economic system that is materialistic and independent of moral values, so that the concept of Islamic economics that integrates ethics and spirituality is needed. With the method of literature study and the approach of Maqāṣid al-Syarī'ah, this study examines al-Maududi's works and compares them with relevant literature. The results of the study show that morality in al-Maududi's thought is not just an additional norm, but the main foundation of Islamic economics that emphasizes justice, balance, and social responsibility. These findings confirm the fundamental differences between Islamic and conventional economics, while providing practical implications that the implementation of modern Islamic economics must prioritize the integration of moral values in economic policies and practices.